Intratendinous Air Phenomenon: A New Ultrasound Marker of Tendon Damage? - Rutkauskas, Saulius; Paleckis, Vidas; Skurvydas, Albertas; Satkunskiene, Danguole; Brazaitis, Marius; Snieckus, Audrius; Baranauskiene, Neringa; Rancevas, Ruslanas; Kamandulis, Sigitas (Frontiers in Physiology, 2017)
Purpose To explore the presence of intratendinous air in physically active males after different types of strenuous physical exercise. Materials and Methods To detect foci (air bubbles) in the quadriceps femoris tendon (QFT) and the proximal and distal parts of the patellar tendon, ultrasound examination was performed under two conditions: 1) after high-intensity cycling on a cycle ergometer (metabolic); 2) after 200 drop jumps (exercise-induced muscle damage). Based on the results of these two interventions, the presence of air in the tendons after 100 drop jumps was examined further with frequently repeated ultrasound measurements. Results Foci were detected in exercise-induced muscle damage. Twenty-three of 60 investigated tendons (38.3%) were observed to contain hyperechoic foci after 100 drop jumps. QFT foci were present in 13/23 cases (56.5%). The location of foci in the QFT was mostly lateral and centro-lateral (76.9%). The foci disappeared completely between 40 and 180 min after completing 100 drop jumps. Conclusions The presence of intratendinous air seems related to high-magnitude, high-force, high-strain exercise of the particular tendon areas. It might represent the stress response of tendons to overload condition.